Sufism in the Light of Orientalism - Uždavinys, Algis (Acta Orientalia Vilnensia, 2005)
Research Institute of Culture, Philosophy, and Arts, VilniusThis article offers a discussion of the problems regarding different interpretations of Sufism, especially those promoted by the 19th century Orientalists and modern scholars. Contrary to the prevailing opinions of those European writers who “discovered” Sufism as a kind of the Persian poetry-based mysticism, presumably unrelated to Islam, the Sufis themselves (at least before the Western cultural expansion) regarded Sufism as theinmost kernel of Islam and the way of the Prophet himself.